Acceptability of an experiential learning laboratory for aspiring entrepreneurs in San Beda College - Jimenez, Caryl Charlene Escolar (Animo Repository, 2014)
Entrepreneurship education requires a supportive environment that is conducive to learning. Essentially, the teaching style is action-oriented and accompanied by the practical application of the concepts and theories discussed in the classroom. The practical or applied learning is a key component to the improvement of an entrepreneurial environment in an educational institution. One of the more popular manifestations of applied learning in entrepreneurship education is through experiential learning laboratories or more popularly called student enterprise centers. There is now a proliferation of experiential learning laboratories in many colleges and universities all over the world. In the Philippines, Ateneo de Manila University has successfully put up a student enterprise center in its Loyola campus. It is in this light that the researchers studied the acceptability of concretizing and improving an entrepreneurial environment in San Beda College Alabang through the conversion of the gazebos located in the college parking area to stalls or kiosks managed by the college students. The 9-item acceptability indicators for the proposed student enterprise center reveal positive results. The students approved the proposed student enterprise center based on their willingness to test their business skills in a hands-on environment. Majority of the students also agreed to convert the gazebos into stalls or kiosks to be managed by the students. Majority of the students would like to engage in the food business and are willing to rent between 15,000- 20,000 per month, on a semestral basis. Majority of the students are willing to devote their time and financial resources for the business, submit their business proposals and comply with business requirements. The projected demand and supply of the proposed student enterprise center on a five-year period shows the potential to succeed if it will push through. There is a significant relationship between the year level of students and the following acceptability indicators: being business-minded, willing to engage in a hands-on environment, conversion of the gazebos to kiosks, the kind of business they are going to put up, the willingness to rent the kiosk and the amount of lease.